Preparation method and application of controllably constructed two-dimensional silicon dioxide nanosheet

By adopting the preparation method of controlling construction of two-dimensional silica nanosheets in the negative electrode materials of lithium-ion batteries, and using liquid phase method and thermal rupture technology, the problem of electrochemical performance deterioration in the charging and discharging process of SiO2 materials is solved, and the preparation of high-performance two-dimensional SiO2@C nanosheet composite materials is realized, which is suitable for lithium-ion battery negative electrode materials.

CN119528161APending Publication Date: 2025-02-28GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411775732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode material SiO2 deteriorates electrochemical performance during charging and discharging, and it is difficult to prepare two-dimensional SiO2 nanosheets through traditional methods, limiting its large-scale application.

Method used

A method of controlling the preparation of two-dimensional SiO2 nanosheets is adopted to realize the preparation of two-dimensional SiO2 nanosheets by the preparation of transition metal oxide @SiO2, calcining treatment of nanosheets and carbon coating modification. This method uses "bottom-up" liquid phase method and thermal rupture technology to overcome the limitations of traditional methods and provide the possibility of large-scale production.

Benefits of technology

The two-dimensional SiO2@C nanosheet composite material prepared by this method significantly improves the electrochemical performance of the negative electrode material of lithium-ion battery, including capacity retention, long cycle performance and rate performance, and has commercial scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528161A_ABST
    Figure CN119528161A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a controllably constructed two-dimensional silicon dioxide nanosheet, and relates to the technical field of preparation of lithium ion battery negative electrode materials, and the preparation method comprises the three steps of preparation of transition metal oxide coated SiO2, preparation of the nanosheet and carbon coating modification. The two-dimensional SiO2 nanosheet is controllably constructed through a thermal cracking technology, the thickness of the obtained sheet structure is adjustable, and a liquid phase method from bottom to top provides possibility for large-scale production. The technology has expandability and flexibility required by commercialization, can be popularized to preparation processes of other two-dimensional nano materials, provides a new thought for controllable construction of a two-dimensional structure, and further, the two-dimensional structure can shorten the diffusion distance of ions and realize rapid transmission of Li < + >, and can be applied to preparation of the two-dimensional nano materials. In addition, aggregation or accumulation in the charging and discharging process can be effectively avoided, and an initial active surface and an open Li < + > transmission channel are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode material preparation, and in particular to a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet and its application. Background Art

[0002] Against the backdrop of the depletion of fossil fuels and the increasing environmental pollution, the exploration of efficient and environmentally friendly lithium-ion batteries has become a trend of the times. At present, the most widely used negative electrode material is graphite. However, after decades of development, its actual capacity is much lower than the theoretical capacity (372 mAh g -1 ) is almost the same as that of lithium-ion batteries, which cannot meet the growing demand for high energy density lithium-ion batteries. Silicon dioxide (SiO2) material is considered to be one of the most promising anode materials for large-scale industrial applications, with a theoretical capacity of up to 1965 mAh g -1 However, in addition to poor electronic conductivity, SiO2 materials still face challenges such as huge volume changes and complex interface reactions due to the lithium insertion mechanism of alloying, which seriously restricts their large-scale application.

[0003] Therefore, silicon-carbon composite negative electrode materials with special structural design have great potential in practical applications. The introduction of carbon effectively improves the overall electronic conductivity and adapts to the significant volume change of SiO2 materials during lithium insertion / extraction. In addition, carbon materials can also enhance the overall structural stability. In order to obtain SiO2 materials with excellent electrochemical properties, researchers have done a lot of work. By reducing the size of SiO2 materials to nanoscale through novel structural design, it can not only effectively alleviate mechanical fracture, but also optimize the interaction between electrons and lithium ions (Li + ) diffusion channels. Many nanomaterials, such as core-shell structures, porous structures, and two-dimensional structures, have shown excellent performance in energy storage.

[0004] Unlike three-dimensional bulk materials, the thickness of two-dimensional materials is within a single or multiple atoms, and the overall lateral arrangement is infinite and orderly. However, according to research in recent years, materials with a sheet structure and a longitudinal thickness of nanometers can be called two-dimensional materials. Based on their own characteristics, two-dimensional materials have shown incomparable advantages in many fields, such as: size constraints of charge carriers, anisotropic electronic and magnetic responses, nonlinear optical properties, excellent mechanical strength and flexibility, and catalytic behavior depending on the cross-section. Therefore, two-dimensional SiO2 nanosheets have unique advantages as negative electrode materials for lithium-ion batteries. The two-dimensional structure can not only shorten the diffusion distance of ions and realize the rapid transmission of Li+, but also effectively avoid aggregation or accumulation during the charge and discharge process, maintaining the initial active surface and open Li + Transmission channel.

[0005] Unfortunately, since SiO2 does not have a corresponding bulk layer, it cannot be obtained by traditional exfoliation methods. To date, atomic deposition and molecular beam epitaxy are the only two methods for preparing two-dimensional SiO2 nanomaterials "from top to bottom". The harsh experimental conditions and precise instrument requirements cannot be adapted to today's industrial system. Fortunately, the "bottom-up" wet chemical method has opened up a new path for the preparation of two-dimensional SiO2 nanomaterials. Although many researchers have conducted some explorations, the controlled synthesis of two-dimensional SiO2 nanomaterials still faces huge challenges. Therefore, the present invention proposes a preparation method and application of controllable construction of two-dimensional silicon dioxide nanosheets to solve the problems existing in the prior art. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to propose a method for preparing and applying a controllably constructed two-dimensional silica nanosheet. This method for preparing and applying a controllably constructed two-dimensional silica nanosheet has the advantage of improving the deterioration of the electrochemical properties of SiO2 materials during the charging and discharging process. The "bottom-up" liquid phase method provides the possibility for large-scale production and solves the problems existing in the prior art.

[0007] To achieve the purpose of the present invention, the present invention is implemented by the following technical scheme: a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: Step 1: Preparation of transition metal oxide @SiO2 Prepare transition metal oxide nanoparticles and disperse them in a liquid phase to obtain a dispersion, then adjust the pH value, slowly drop a silicon source, and stir the reaction solution to react, and after the reaction, filter, wash and dry to obtain transition metal oxide @SiO2; Step 2: Preparation of nanosheets The transition metal oxide @SiO2 is rapidly heated and calcined at high temperature, and then the transition metal oxide is removed by acid washing, and then filtered, washed and dried to obtain a two-dimensional SiO2 nanosheet; Step 3: Carbon coating modification A carbon source was selected and the obtained two-dimensional SiO2 nanosheets were carbon-coated and modified to obtain SiO2@C composite materials.

[0008] A further improvement is that in step 1, the transition metal oxide nanoparticles include one of zinc oxide, tin oxide, copper oxide, titanium dioxide, and manganese dioxide, and the silicon source includes one of tetraethyl orthosilicate, sodium metasilicate, and aluminum silicate.

[0009] Further improvement is that: in the step 1, the content of transition metal oxide in the dispersion is 2-10%, the pH value of the dispersion is 7-10, and the concentration of silicon source in the dispersion is 0.2-0.7 mol / L-1 .

[0010] A further improvement is that in step 1, the reaction temperature is 15-100° C. and the reaction time is 2-10 h.

[0011] A further improvement is that in step 1, the drying process is carried out in a vacuum oven at 60-200°C.

[0012] A further improvement is that in step 2, the heating rate is 5-30°C min -1 The temperature is 600-1200° C. and the time is 1.5-3.5 hours. The high temperature calcination temperature is 600-1200° C. and the time is 1-8 hours, and it needs to be carried out in an inert atmosphere.

[0013] A further improvement is that in step 2, the acid used for pickling is one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the concentration is 0.5 to 2 mol / L.

[0014] A further improvement is that in step three, the carbon source includes one or more of m-diphenol, formaldehyde, citric acid, carbon nanotubes, glucose, and tartaric acid.

[0015] A method for preparing two-dimensional silicon dioxide nanosheets with controllable construction is applied in negative electrode materials of lithium-ion batteries.

[0016] The beneficial effects of the present invention are as follows: the present invention proposes a thermal rupture technology based on the difference in thermal expansion coefficients, and prepares two-dimensional SiO2 nanosheets "from the bottom up". The thickness of the obtained sheet structure is adjustable, and the "bottom-up" liquid phase method provides the possibility for large-scale production. The thermal rupture technology provides a new idea for the controllable construction of 2D structures.

[0017] Furthermore, the so-called thermal cracking technology cleverly utilizes the huge difference in thermal expansion coefficient between the template and the target material (for example: α ZnO = 10.2 × 10 -6 ℃ -1 , α SiO2 = 0.55 × 10 -6 ℃ -1 ), after using ZnO nanorods as a hard template and depositing a thin SiO2 layer, the internal ZnO template expands rapidly due to heat, stretching the external SiO2 layer and breaking it into a flaky structure.

[0018] Furthermore, the two-dimensional structure can not only shorten the diffusion distance of ions, but also realize Li + It can effectively avoid the aggregation or accumulation during the charge and discharge process, maintain the initial active surface and open Li +The technology has the scalability and flexibility required for commercialization and can be extended to the preparation process of other two-dimensional nanomaterials.

[0019] The two-dimensional SiO2@C nanosheet composite material provided by the present invention is used as a negative electrode material for lithium-ion batteries. The negative electrode made of the two-dimensional SiO2@C nanosheet composite material as a raw material is subjected to electrochemical testing. The capacity retention rate can reach more than 97% during charge and discharge at a low current density; the long cycle performance is excellent and the stability is good at a high current density; the rate performance is excellent at different current densities and the structure is stable; the application of the hollow mesoporous SiO2@C nanosphere composite material of the present invention as a negative electrode material for lithium-ion batteries can significantly improve the first coulomb efficiency of the SiO2 material by 20-30%, and the coulomb efficiency rapidly approaches 100% in subsequent cycles, and remains stable for hundreds of cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the steps of the present invention. Figure 2 Schematic diagram of a scanning electron microscope of a two-dimensional SiO2 nanosheet according to the first embodiment of the present invention. Figure 3 It is a schematic diagram of the cycle performance curve of the two-dimensional SiO2@C composite material of Example 3 of the present invention at a current density of 0.1 A / g. Figure 4 It is a schematic diagram of the cycle performance curve of the two-dimensional SiO2@C composite material of Example 4 of the present invention at a current density of 1 A / g. Figure 5 It is a schematic diagram of the rate performance curve of the two-dimensional SiO2@C composite material of Example 5 of the present invention. DETAILED DESCRIPTION

[0021] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0022] The following materials were purchased commercially. Example

[0023] according to Figure 1 and Figure 2 As shown, this embodiment proposes a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: 120 mL of deionized water and 4 mL of ammonia water were placed in a beaker, and 1.2 g of ZnO nanoparticles were added. After ultrasonic dispersion, 2.8 mL of ethyl orthosilicate was slowly added. Stirring was continued at room temperature for 3 h. The resulting white suspension was centrifuged, washed, and dried in a 60 °C oven for 12 h. The resulting white powder was transferred to a crucible and heated in air at 20 °C min -1The temperature was rapidly raised to 900℃ at a heating rate of 1 mol L -1 The ZnO template was removed by washing with hydrochloric acid, and two-dimensional SiO2 nanosheets were obtained after filtration, washing and drying. 0.1g glucose was dissolved in a solution containing 50mL ethanol and 5mL water, and 0.2g of the obtained two-dimensional SiO2 nanosheets was added. After being stirred dry at room temperature, it was transferred into a crucible and calcined at 800℃ in a tube furnace for 2.5h to obtain SiO2@C composite materials. Example

[0024] according to Figure 1 As shown, this embodiment proposes a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: 120 mL of ethanol and 1.5 mL of sodium hydroxide were placed in a beaker, and 1.2 g of SnO2 nanoparticles were added. After ultrasonic dispersion, 2.5 mL of vinyl tri(β-methoxyethoxy)silane was slowly added. Stirring was continued at room temperature for 8 h. The resulting white suspension was centrifuged, washed, and dried in an oven at 100 °C for 8 h. The resulting white powder was transferred to a crucible and heated at 30 °C min under an argon atmosphere. -1 The temperature was rapidly raised to 700℃ at a heating rate of 3 h. -1 The prepared two-dimensional SiO2 nanosheets were ultrasonically dispersed in a solution containing 20 mL of ethanol and 10 mL of water, and 0.3 g of resorcinol and 0.2 mL of ammonia water were added in sequence, and stirred for 20 min to mix them evenly. Subsequently, 0.3 ml of formaldehyde was added, and stirring was continued at 40 ° C for 15 h, filtered, washed, dried, and placed in a tube furnace for calcination at 750 ° C for 2.5 h to obtain a SiO2@C composite material. Example

[0025] according to Figure 1 and Figure 3 As shown, this embodiment proposes a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: Measure 120mL of isopropanol and 2.5mL of sodium bicarbonate and place them in a beaker. Add 1.2g of TiO2 nanoparticles and slowly drop 3mL of sodium metasilicate after ultrasonic dispersion. Continue stirring at room temperature for 7h. The resulting white suspension is centrifuged, washed, and dried in an oven at 80℃ for 10h. The resulting white powder is transferred to a crucible and heated at 15℃ min under a nitrogen atmosphere. -1 The temperature was rapidly raised to 1000℃ at a heating rate of 1.5h. -1The TiO2 template was removed by washing with hydrofluoric acid, and two-dimensional SiO2 nanosheets were obtained after filtration, washing and drying. 0.1 g of carbon nanotubes were ultrasonically dispersed in a solution containing 50 mL of ethanol and 5 mL of water, and 0.2 g of the obtained two-dimensional SiO2 nanosheets were added, and stirring was continued for 2 h, and then filtered, washed and vacuum dried to obtain SiO2@C composite materials. Example

[0026] according to Figure 1 and Figure 4 As shown, this embodiment proposes a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: 150 mL of deionized water and 6 mL of ammonia water were placed in a beaker, and 1.2 g of CuO nanoparticles were added. After ultrasonic dispersion, 2 mL of aluminum silicate was slowly added. Stirring was continued at room temperature for 5 h. The resulting white suspension was centrifuged, washed, and dried in an oven at 80 °C for 10 h. The resulting white powder was transferred to a crucible and heated in air at 5 °C min -1 The temperature was rapidly raised to 1000℃ at a heating rate of 2.5h. -1 The CuO template was removed by washing with hydrochloric acid, and two-dimensional SiO2 nanosheets were obtained after filtration, washing and drying. 0.1g of tartaric acid was dissolved in a solution containing 50mL of ethanol and 5mL of water, and 0.2g of the obtained two-dimensional SiO2 nanosheets was added. After being stirred dry at room temperature, the mixture was transferred to a crucible and calcined at 800℃ in a tube furnace for 2.5h to obtain a SiO2@C composite material. Example

[0027] according to Figure 1 and Figure 5 As shown, this embodiment proposes a method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, comprising the following steps: 120 mL of ethanol and 4.2 mL of ammonia water were placed in a beaker, and 1.2 g of MnO2 nanoparticles were added. After ultrasonic dispersion, 2 mL of ethyl orthosilicate was slowly added. Stirring was continued at room temperature for 5 h. The resulting white suspension was centrifuged, washed, and dried in a 60 °C oven for 12 h. The resulting white powder was transferred to a crucible and heated in air at 25 °C min -1 The temperature was rapidly raised to 900℃ at a heating rate of 1.5 mol L -1 The two-dimensional SiO2 nanosheets were obtained by washing with sulfuric acid to remove the MnO2 template, filtering, washing and drying. 0.1g of citric acid was dissolved in a solution containing 70mL of ethanol and 5mL of water, and 0.2g of the obtained two-dimensional SiO2 nanosheets was added. After being stirred dry at room temperature, the mixture was transferred to a crucible and calcined at 850℃ in a tube furnace for 2.5h to obtain a SiO2@C composite material. Example

[0028] according to Figure 1 As shown, this embodiment proposes a method for preparing a two-dimensional silicon dioxide nanosheet that can be controlled to be constructed, which is the same as the first embodiment, and the difference from the first embodiment is that the temperature is 30°C min in air. -1 The temperature was rapidly raised to 1200℃ at a heating rate of 1 mol L -1 The ZnO template was removed by washing with hydrochloric acid, and two-dimensional SiO2 nanosheets were obtained after filtration, washing and drying. 0.1g glucose was dissolved in a solution containing 50mL ethanol and 5mL water, and 0.2g of the obtained two-dimensional SiO2 nanosheets was added. After being stirred dry at room temperature, it was transferred into a crucible and calcined at 600℃ in a tube furnace for 8h to obtain SiO2@C composite materials. Example

[0029] according to Figure 1 As shown, this embodiment proposes a method for preparing a two-dimensional silicon dioxide nanosheet that can be controlled to be constructed, which is the same as the first embodiment, and the difference from the first embodiment is that the temperature is 5°C min in air. -1 The temperature was rapidly raised to 600℃ at a heating rate of 1 mol L -1 The ZnO template was removed by washing with hydrochloric acid, and two-dimensional SiO2 nanosheets were obtained after filtration, washing and drying. 0.1g glucose was dissolved in a solution containing 50mL ethanol and 5mL water, and 0.2g of the obtained two-dimensional SiO2 nanosheets was added. After being stirred dry at room temperature, it was transferred into a crucible and calcined at 1200℃ in a tube furnace for 1h to obtain SiO2@C composite materials.

[0030] The two-dimensional SiO2@C nanosheet composite material provided by the present invention is used as a negative electrode material for lithium-ion batteries. The negative electrode made of the two-dimensional SiO2@C nanosheet composite material as a raw material is subjected to electrochemical testing. The capacity retention rate can reach more than 97% during charge and discharge at a low current density; the long cycle performance is excellent and the stability is good at a high current density; the rate performance is excellent at different current densities and the structure is stable; the application of the hollow mesoporous SiO2@C nanosphere composite material of the present invention as a negative electrode material for lithium-ion batteries can significantly improve the first coulomb efficiency of the SiO2 material by 20-30%, and the coulomb efficiency rapidly approaches 100% in subsequent cycles, and remains stable for hundreds of cycles.

[0031] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the framework and scope of application of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet, characterized in that: The following steps are involved: Step 1: Preparation of transition metal oxide @SiO2 Prepare transition metal oxide nanoparticles and disperse them in a liquid phase to obtain a dispersion, then adjust the pH value, slowly drop a silicon source, and stir the reaction solution to react, and after the reaction, filter, wash and dry to obtain transition metal oxide @SiO2; Step 2: Preparation of nanosheets The transition metal oxide @SiO2 is rapidly heated and calcined at high temperature, and then the transition metal oxide is removed by acid washing, and then filtered, washed and dried to obtain a two-dimensional SiO2 nanosheet; Step 3: Carbon coating modification A carbon source was selected and the obtained two-dimensional SiO2 nanosheets were carbon-coated and modified to obtain SiO2@C composite materials.

2. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 1, the transition metal oxide nanoparticles include one of zinc oxide, tin oxide, copper oxide, titanium dioxide, and manganese dioxide, and the silicon source includes one of tetraethyl orthosilicate, sodium metasilicate, and aluminum silicate.

3. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 1, the content of transition metal oxide in the dispersion is 2-10%, the pH value of the dispersion is 7-10, and the concentration of silicon source in the dispersion is 0.2-0.7 mol / L -1 .

4. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 1, the reaction temperature is 15-100° C. and the reaction time is 2-10 hours.

5. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 1, the drying process is carried out in a vacuum oven at 60-200°C.

6. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 2, the heating rate is 5-30°C min -1 The temperature is 600-1200° C. and the time is 1.5-3.5 hours. The high temperature calcination temperature is 600-1200° C. and the time is 1-8 hours, and it needs to be carried out in an inert atmosphere.

7. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 2, the acid used for pickling is one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the concentration is 0.5 to 2 mol / L.

8. The method for preparing a controllably constructed two-dimensional silicon dioxide nanosheet according to claim 1, characterized in that: In the step 3, the carbon source includes one or more of m-diphenol, formaldehyde, citric acid, carbon nanotubes, glucose, and tartaric acid.

9. Application of the method for preparing controllably constructed two-dimensional silicon dioxide nanosheets according to any one of claims 1 to 8 in negative electrode materials for lithium-ion batteries.